Elsholtzia ciliata Essential Oil Exhibits a Smooth Muscle Relaxant Effect - Irma Martišienė; Vilma Zigmantaitė; Lauryna Pudžiuvelytė; Jurga Bernatonienė; Jonas Jurevičius (MDPI AG, 2023)
A recent in vivo study in pigs demonstrated the hypotensive properties of essential oil extracted from the blossoming plant Elsholtzia ciliata. This study was designed to examine the effect of E. ciliata essential oil (EO) on smooth muscle contraction. Tension measurements were performed on prostate strips and intact aortic rings isolated from rats. Results showed that EO caused a concentration-dependent reduction in phenylephrine-induced contraction of both the prostate and aorta, with a more pronounced inhibitory effect in the prostate. The IC50 of EO for the prostate was 0.24 ± 0.03 µL/mL (n = 10) and for the aorta was 0.72 ± 0.11 µL/mL (n = 4, p < 0.05 vs. prostate). The chromatographic analysis identified elsholtzia ketone (10.64%) and dehydroelsholtzia ketone (86.23%) as the predominant compounds in the tested EO. Since both compounds feature a furan ring within their molecular structure, other furan ring-containing compounds, 2-acetylfuran (2AF) and 5-methylfurfural (5MFF), were examined. For the first time, our study demonstrated the relaxant effects of 2AF and 5MFF on smooth muscles. Further, results showed that EO, 2AF, and 5MFF altered the responsiveness of prostate smooth muscle cells to phenylephrine. Under control conditions, the EC50 of phenylephrine was 0.18 ± 0.03 µM (n = 5), while in the presence of EO, 2AF, or 5MFF, the EC50 values were 0.81 ± 0.3 µM (n = 5), 0.89 ± 0.11 µM (n = 5), and 0.69 ± 0.23 µM (n = 4), respectively, p < 0.05 vs. control. Analysis of the affinity of EO for α1-adrenergic receptors in the prostate suggested that EO at a certain range of concentrations has a competitive antagonistic effect on α1-adrenergic receptors. In conclusion, EO elicits a relaxant effect on smooth muscles which may be related to the inhibition of α1-adrenoreceptors.